Effect of internal electric field on non‐radiative carrier recombination in the strain‐balanced InGaAs/GaAsP multiple quantum well solar cells. Issue 2 (10th January 2014) - Fukuyama, Atsuhiko; Aihara, Taketo; Yokoyama, Yuki; Kojima, Michiya; Fujii, Hiromasa; Suzuki, Hidetoshi; Sugiyama, Masakazu; Nakano, Yoshiaki; Ikari, Tetsuo
<x xml:space="preserve">Abstract</x> Effect of an internal built‐in electric field on the non‐radiative recombination process of strain‐balanced InGaAs/GaAsP multiple quantum wells (MQWs) inserted into a GaAs p–i–n solar cell structure was investigated using the piezoelectric photo–thermal technique. From the experimental data obtained from two types of p–i–n solar cell structures with partly charge‐neutral and uniform‐gradient potentials, the decrease in the built‐in electric field contributed to the decrease in the non‐radiative carrier recombination in the MQW. This phenomenon was especially pronounced in the higher photon energy of the incident light and in large quantum well stack number. With the increase in the photon energy, the penetration length shortened, and most carriers were generated in the charge‐neutral area in the i‐region. The present experimental results could be understood by the increase in the radiative recombination processes within the MQW because of the wave function overlap is essentially unity.